2013
DOI: 10.4236/ijoc.2013.33021
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the Cyclization of 5-Hexenyl, 3-Oxa-5-Hexenyl and 4-Oxa-5-Hexenyl Radicals

Abstract: The intramolecular cyclization of 5-hexenyl radicals continues to be an important synthetic method for the construction of five-membered rings. The synthetic utility arises from the high degree of regioselectivity to give predominantly cyclopentyl products in high yield under mild conditions. Recently we reported product cyclization studies on 4-oxa perturbed 5-hexenyl radical. In this paper, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Table shows that although the calculated transition state free energies for cyclization of radicals 13 and 14 are slightly different from those reported in the literature, they all follow the same expected trends; that is a lower transition state free energy for the 5-exo cyclization of 13 than for the 6-exo cyclization of 14 . Both have chairlike transition states and the free energy of the reaction (product) is significantly exergonic in both cases.…”
Section: Results and Discussioncomputationalmentioning
confidence: 46%
See 2 more Smart Citations
“…Table shows that although the calculated transition state free energies for cyclization of radicals 13 and 14 are slightly different from those reported in the literature, they all follow the same expected trends; that is a lower transition state free energy for the 5-exo cyclization of 13 than for the 6-exo cyclization of 14 . Both have chairlike transition states and the free energy of the reaction (product) is significantly exergonic in both cases.…”
Section: Results and Discussioncomputationalmentioning
confidence: 46%
“…This has been previously described in the literature as a kinetic effect. 21 Since the substituents increase the number of gauche interactions in the open chain system, both ΔH and − TΔS decrease for the transition state and product. This can also be observed in the less endergonic cyclization reactions of 18 and 19 compared to 17 (Table 3).…”
Section: ■ Results and Discussioncomputationalmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 For 5-exo-closures this TS resembles the comparatively strain-free chair conformation of the cyclohexane ring 2 with the radical centre (X-1) approaching C-5 of the alkene at an angle close to tetrahedral. A number of computational studies of hex-5-enyl ring closures have been reported [20][21][22][23][24] and these have generally supported Beckwith-Houk type TS models. Computational studies of the ring closures of carbonyl radicals, 25 iminyl radicals, 13 aminyl radicals 26 and oxyl radicals 15 have generally focused either on the exo vs. endo regioselectivity or on details of the stereochemistry induced by substituents.…”
Section: Introductionmentioning
confidence: 85%
“…3 The main characteristics of the reaction were delineated in a seminal article by Beckwith and Ingold in 1980. the cyclohexane ring 2 with the radical centre (X-1) approaching C-5 of the alkene at an angle close to tetrahedral. A number of computational studies of hex-5-enyl ring closures have been reported [20][21][22][23][24] and these have generally supported…”
Section: Introductionmentioning
confidence: 88%